A Novel Approach Using Model Predictive Control to Enhance the Range of Electric Vehicles. (2016) - Eckstein, Julian; Lüke, Christopher; Brunstein, Frederik; Friedel, Patrick; Köhler, Ulrich; Trächtler, Ansgar
Abstract: The energy consumption of comfort components influences the range of electric vehicles significantly. Thus, intelligent power distribution is required. In this contribution a piece-wise linear model predictive controller is proposed which influences the heating ventilation and air-conditioning. Predictive route data is used to identify high power demands in the drivetrain. The controller ensures a defined comfort level while reducing the power loss of the traction battery. To enable real-time capability a sophisticated driver cabin model is linearized and used in a bilinear optimization. The control performance is evaluated in detail and conclusions are drawn for further development.